Sources of risk communication, knowledge and preventive practices toward Lassa fever in Bauchi State, Nigeria - Benjamin Bukky Ilesanmi; Nathanael Afolabi; Olayinka Badmus; Munkail Titilola; Abdulmajid Ahmad; Usman Inuwa; Matthew Okoh; Hajara Aliyu; Shittu Abdu-Aguye; Foyeke Oyedokun-Adebagbo (Discover Public Health)
Abstract Background Lassa fever (LF) is a zoonotic disease that persistently threaten public health and Bauchi is among the most affected states in Nigeria. Knowledge and preventive practices are the recommended strategies to prevent LF transmission. We examined the level and sources of risk communication influencing knowledge and preventive practices towards Lassa fever (KPLF) and determined its associated factors in Bauchi state. Methods A cross-sectional study was conducted. Multistage sampling technique was used to select the respondents. We analysed data of 1173 respondents aged 18 years and above who have heard of LF. Composite and median statistics were used to compute KPLF and was dichotomized into low and high. Percentage and frequency were used to describe all the variables and binary logistic regression models were fitted to examine sources of risk communication and factors associated with KPLF at 95% confidence interval. Results High proportion (26.43%) of the respondents were aged 30–39 years, belong to Hausa ethnic group (49.62%), had formal education (61.38%) and were rural residents (68.80%). Approximately 82.0% had high knowledge of LF (KLF), 64.71% had high preventive practices towards LF (PLF) and overall 54.65% had high KPLF. Radio (AOR:1.56, 95% CI 1.05–2.30), health workers (UOR:1.40, 95% CI 1.40, 95% CI 1.10–1.78), and newspaper/flyers (AOR:3.84, 95% CI 1.64–8.96) are sources of risk communication with significant elevated odds associated with high KPLF. Age group 60 years and above (AOR:3.02, 95% CI 1.22–7.45), being a Fulani (AOR:1.51, 95% CI 1.07–2.16), a high wealth status (AOR:1.44, 95% CI 1.07–1.94), being a respondent from Bauchi (AOR:1.73, 95% CI:1.05–2.83) and Toro (AOR:2.78, 95% CI 1.70–4.54) have significant elevated odds associated with high KPLF. Conclusion More than half have high KPLF, a substantial proportion still has low KPLF. To sustain high KPLF and increase it, radio, health workers and newspaper/flyers as sources of risk communication should be continuously adopted and socio-demographic factors should be considered in the choice of risk communication strategies to disseminate risk communication messages on LF.